Antioxidant protection of a polysaccharide produced by Chaetomium globosum CGMCC 6882 on H2O2-challenged HepG2 cells - Zichao Wang; Yi Zheng; Wenzhuo Lu; Jinchu Yang; Yingjie Feng; Zhitao Li; Na Li; Yahui Yang; Qi Wang; Lemei An (Carbohydrate Polymer Technologies and Applications)
Effective utilization of waste kitchen oil (WKO) is important to environmental protection and economic development. Presently, an endophytic fungus Chaetomium globosum CGMCC 6882 polysaccharide (CGP-WKO) was successfully produced through submerged fermentation with the sole carbon source of WKO. CGP-WKO had a yield of 1.53 ± 0.27 g/L and contained 95.85 % ± 3.02 % carbohydrate and 2.94 % ± 0.62 % protein. Structural feature analysis indicated that CGP-WKO contained glucose, glucosamine, mannose, rhamnose, galactose, fructose, and glucuronic acid in a molar ratio of 30.38: 1.34: 32.22: 9.68: 1.59: 0.62: 3.73. The weight-averaged molecular weight of CGP-WKO was 26.64 kDa, and its polydispersity was 1.48. Moreover, antioxidant capacity detection in vitro demonstrated that when the concentration of CGP-WKO was 1.0 mg/mL, its scavenging effects against 1,1-diphenyl-2-picrylhydrazyl; 2,2′-azinobis-di-(3-ethyl-benzothiazolin-6-sulfonic acid) diammonium salt; and hydroxyl and superoxide radicals were 45.89 % ± 1.89 %, 55.89 % ± 1.12 %, 29.02 % ± 2.61 %, and 52.76 % ± 2.12 %, respectively; and the IC50 values were 6.4612, 0.8888, 13.8585, and 0.9398 mg/mL, respectively. CGP-WKO increased the content of superoxide dismutase, catalase, and glutathione peroxidase and reduced malondialdehyde content in H2O2-challenged HepG2 cells. Overall, the present work indicated that CGP-WKO can be used as an antioxidant agent in the food, cosmetics, and pharmaceutical industries.